Electronic applications of the Smith Chart in waveguide, circuit, and component analysis - Smith, Phillip H. 1905- (SciTech Publishing, Inc., 1995)
This is the second edition of Electronic Applications of the Smith Chart, written by Phillip H. Smith, the originator of the Smith Chart. It covers the history, development and applications of the Smith Chart. This classic reference book describes how the chart is used for designing lumped element and transmission line circuits. The text provides tutorial material on transmission line theory and behavior, circuit representation on the chart, matching networks, network transformations and broadband matching. This edition includes a new chapter with example designs and description of the winSMITH software accessory.